1996
DOI: 10.1007/s002130050119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxazepam and lorazepam on implicit and explicit memory: evidence for possible influences of time course

Abstract: The effects of oxazepam (30 mg), lorazepam (2 mg), and placebo on implicit and explicit memory were studied in two testing cycles, 100 and 170 min after drug administration. Thirty healthy volunteers were randomly assigned to one of three groups (placebo, oxazepam, or lorazepam) in a double-blind, independent groups design. Drug groups were equivalent prior to drug administration on a variety of cognitive measures. Following drug administration, both oxazepam and lorazepam equally impaired performance on a cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 40 publications
(83 reference statements)
5
33
1
Order By: Relevance
“…However, as this area was not activated during the explicit memory condition per se, it is unlikely to be of significance with regard to the understanding of this type of memory processing. Although benzodiazepines do not generally impair performance in the word-stem completion test, lorazepam and oxazepam have been reported to impair performance in this test (Sellal et al 1992;Stewart et al 1996;Vidailhet et al 1996). Although we found no significant impairment, the midazolam group did complete fewer word stems.…”
Section: Discussioncontrasting
confidence: 57%
“…However, as this area was not activated during the explicit memory condition per se, it is unlikely to be of significance with regard to the understanding of this type of memory processing. Although benzodiazepines do not generally impair performance in the word-stem completion test, lorazepam and oxazepam have been reported to impair performance in this test (Sellal et al 1992;Stewart et al 1996;Vidailhet et al 1996). Although we found no significant impairment, the midazolam group did complete fewer word stems.…”
Section: Discussioncontrasting
confidence: 57%
“…Curran and Gorenstein, 1993;Legrand et al, 1995;Stewart et al, 1996;Buffett-Jerrott et al, 1998a,b;Martin et al, 2002). L also had a deleterious effect in the inclusion task, reflecting general BZ amnestic effects (Curran, 1991(Curran, , 2000Buffett-Jerrott and Stewart, 2002), so an alternative explanation for the indirect task impairment would be that L decreased the contribution of explicit memory to performance (see Stewart et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…This lent support to the assertion that L does in fact impair implicit memory. Others (Stewart et al, 1996;Buffett-Jerrott et al, 1998a,b) who compared performance in a direct and indirect stem-completion task also claimed to have shown implicit memory impairment by oxazepam that was not due to contamination of explicit memory. However, these studies did not follow Schacter et al's (1989) paradigm in that there was no manipulation that differently effects implicit and explicit memory such as levels of processing nor measures of baseline completions were included in the direct task; both points weaken their claim.…”
Section: Discussionmentioning
confidence: 95%
“…Possible explanations given for this finding have included a different cortical distribution of lorazepam, or a different population of benzodiazepine receptors uniquely affected by lorazepam (Curran et al 1987;Knopman 1991;Sellal et al 1992;Curran and Gorenstein 1993). In the last few years, some research has indicated that lorazepam may not be the only benzodiazepine which impairs priming (Vidailhet et al 1994;Legrand et al 1995;Stewart et al 1996). For example, Legrand and associates found that diazepam impaired priming when implicit memory was tested near the peak blood concentration for diazepam (i.e., 60 min post-drug).…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, Curran and Gorenstein's memory testing at 120 min after drug administration may have been too early to have detected any impairments of oxazepam on implicit memory. Stewart et al (1996) compared the effects of oxazepam (30 mg) and lorazepam (2 mg) at two time points (100 and 170 min post-drug) on tests of implicit and explicit memory to investigate the potential time-dependent effects of these drugs. Stewart et al (1996) used a cued recall test of explicit memory and a word stem completion test of implicit memory.…”
Section: Introductionmentioning
confidence: 99%